Keystream Generator Based On Simulated Annealing - Ayad A. Abdulsalam (Journal of Applied Computer Science & Mathematics, 2011)
Advances in the design of keystream generator using heuristic techniques are reported. A simulated annealing algorithm for generating random keystream with large complexity is presented. Simulated annealing technique is adapted to locate these requirements. The definitions for some cryptographic properties are generalized, providing a measure suitable for use as an objective function in a simulated annealing algorithm, seeking randomness that satisfy both correlation immunity and the large linear complexity. Results are presented demonstrating the effectiveness of the method.